2019
DOI: 10.1002/jor.23821
|View full text |Cite
|
Sign up to set email alerts
|

Pathological kinematic patterns of the tarsal complex in stage II adult‐acquired flatfoot deformity

Abstract: The in vivo kinematic characteristics of the tarsal joints during gait stance phase were still unclear in adult-acquired foot deformity (AAFD). This study included seven healthy subjects (fourteen feet) and twelve stage II AAFD patients (fourteen feet). The 3D models of tarsal bones were reconstructed based on CT scan. Each subject took standard gait on the single fluoroscopy system. Continuous lateral fluoroscopic images were collected. The key postures during the stance phase were selected. The 2D-3D registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The image selection procedure was based on a custom-made platform with an embedded force plate, and seven key poses were chosen during one whole gait cycle. The seven selected poses were described in a previous study [21].…”
Section: Methodsmentioning
confidence: 99%
“…The image selection procedure was based on a custom-made platform with an embedded force plate, and seven key poses were chosen during one whole gait cycle. The seven selected poses were described in a previous study [21].…”
Section: Methodsmentioning
confidence: 99%
“…Our study, by utilizing the advanced 3D-to-2D registration technique as well [13,[15][16][17][18], aimed to investigate the motion characteristics of hindfoot joints in the stance phase more comprehensively based on the above mentioned 5 events in stage AAFD. Understanding the biomechanics of the hindfoot is critical to the proper care of patients with a variety of orthopedic impairments and foot deformities resulting from conditions such as cerebral palsy, spina bi da, club foot, traumatic brain injury and spinal cord injury [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al detected Synchronous and homodromous rotational motions of the TNJ, STJ, and CCJ during the stance phase [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hindfoot joints are mainly comprised of three joints, namely the subtalar joint (STJ), the TNJ and the calcaneo-cuboid joint (CCJ). Wang et al detected synchronous and homodromous rotational motions of the TNJ, STJ, and CCJ during the stance phase [ 11 ]. Van de Velde et al showed significant differences in range of motion in patients with flatfoot.…”
Section: Introductionmentioning
confidence: 99%